An Analysis of Politeness Strategies in George W. Bush’s Victory Speeches - Raesky, Aisya Bella; Novitri, Novitri (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2023)
In communicating, people may express themselves in a particular communication channel, spoken or written. For instance, people may use direct and indirect communication as their message’s perceived meaning varies depending on the tone of the messages. As a result, they may apply different levels of politeness. This research investigated politeness strategies used by George W. Bush in his presidential acceptance speeches. The researcher collected the data used in this research from the transcripts of Bush's two victory speeches (2000 and 2004). The analysis based on Brown and Levinson’s (1987) classification of politeness strategies. The research findings showed that George W. Bush applied the positive strategy as his most dominant politeness strategies, such as Pay more attention, give recognition or sympathy to the hearer and Offer helps or promises sub-strategies. This research also revealed the factors affecting Bush's politeness in speaking, among others; social status, interest, and solidarity. However, Bush did not show any unambiguous and disguised manner as he attempted to build the citizens' trust in him.